2022
DOI: 10.3340/jkns.2021.0056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of COVID-19 Outbreak and Changes in Neurosurgical Emergency Patients

Abstract: Objective : COVID-19 has spread worldwide since the first case was reported in Wuhan, China, in December 2019. Our institution is a regional trauma and emergency center in the northern Gyeonggi Province. The changing trend of patient care in the emergency room of this hospital likely reflects the overall trend of patients in the area. In the present study, whether changes in the surrounding social environment following the outbreak of COVID-19 changed the incidence of neurosurgical emergency patients and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…It is thought to be related to coronavirus disease 2019 (COVID-19). Previous studies have reported a decrease in the overall number of trauma patients due to a decrease in non-essential activities during the COVID-19 pandemic, 15 25) and this study also showed similar results.…”
Section: Discussionsupporting
confidence: 89%
“…It is thought to be related to coronavirus disease 2019 (COVID-19). Previous studies have reported a decrease in the overall number of trauma patients due to a decrease in non-essential activities during the COVID-19 pandemic, 15 25) and this study also showed similar results.…”
Section: Discussionsupporting
confidence: 89%
“…The Institutional Review Board (IRB) waived the informed consents for this retrospective study. As a follow-up to the previous study [ 12 ], changes of trends in neurosurgical emergency patients were analyzed as the COVID-19 pandemic continued. The overall trend was analyzed from January 2021 to December 2021.…”
Section: Methodsmentioning
confidence: 99%
“…In July, August, and September of 2020, numbers of patients who underwent spinal surgeries were similar to those of the previous year: 16,572, 15,204, and 14,296 in 2019 vs. 16,800 (101% compared to the previous year), 15,205 (100%), and 14,211 (99%) in 2020, respectively. In October, Novermber, and December of 2020, numbers of patients who underwent spinal surgeries showed an increasing trend compared to those of the previous year: 14,535, 14,608, and 15,678 in 2019 vs. 15,847 (109%), 16,256 (111%), and 16,279 (104%) in 2020, respectively.…”
Section: Number Of Patients Who Underwent Spine Surgeriesmentioning
confidence: 60%
“…The COVID-19 pandemic is affecting all aspects of our daily lives, including hospital visits. According to Lee et al [ 14 ], neurosurgical emergency patients were analyzed, and the number of trauma and stroke paitents decreased as the overall activity decreased. In spine patients, Ham et al [ 9 ] have analyzed the number of daily outpatients from 2017 to March 2020 and found that the number of daily outpatients is decreased significantly compared to that in the same month before the pandemic.…”
Section: Discussionmentioning
confidence: 99%